In vitro toxicity of cationic micelles and liposomes in cultured human hepatocyte (HepG2) and lung epithelial (A549) cell lines. (October 2016) - Roursgaard, Martin; Knudsen, Kristina Bram; Northeved, Helle; Persson, Mikael; Christensen, Tina; Kumar, Pramod E.K.; Permin, Anders; Andresen, Thomas L.; Gjetting, Torben; Lykkesfeldt, Jens; Vesterdal, Lise K.; Loft, Steffen; et al.
Abstract: The aim of this study was to compare the effects of cationic micelle and liposome drug delivery systems on liver and lung cells in a toxicological in vitro screening model, with observations on cytotoxicity and genotoxicity. A screening battery was established for assessment of a broad range of parameters related to adverse effects. Clear concentration response effects were observed related to impairment of mitochondrial function, membrane integrity and oxidative stress markers, but no effect was observed on genotoxicity. The adverse effects were highest for the liposomes. The High Content Screening seems optimal for initial screening of adverse effects, and combined with standard cytotoxicity measurements initial screening can be performed for predictive toxicological screening. Highlights: Nanocarriers show limited toxicological effect at low doses. High Content Screening optimal for screening of compounds with low toxicity Cationic liposomes show more effect than cationic micelles. In vitro screening are relevant as initial evaluation tool for predictive toxicology.